2010
DOI: 10.1111/j.1475-6773.2009.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Has Pay‐for‐Performance Decreased Access for Minority Patients?

Abstract: Despite minimal evidence of minority patient avoidance in the PHQID, monitoring of avoidance should continue for P4P programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 36 publications
0
32
1
3
Order By: Relevance
“…[44][45][46][47] Patient perceived pain control is a key quality indicator for hospitals. Some providers are financially incentivized to aggressively treat pain because their salaries are tied to patient satisfaction scores that encompass pain control metrics.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46][47] Patient perceived pain control is a key quality indicator for hospitals. Some providers are financially incentivized to aggressively treat pain because their salaries are tied to patient satisfaction scores that encompass pain control metrics.…”
Section: Introductionmentioning
confidence: 99%
“…Little evidence about effect of P4P was found in one study [52]. Also one systematic review found that P4P in rural areas, are likely to increase disparities in quality of care and health outcomes [53].…”
Section: Access To Carementioning
confidence: 99%
“…Diabetes outcomes [46] Quasi experimental LDL-C b100 mg/dL: +12 Access to minority patients [52] Before-after little evidence that the PHQID reduced access for minority patients -Disparities in quality [53] Literature review P4P in rural areas, are likely to increase disparities in quality of care & health outcomes.…”
Section: Referencesmentioning
confidence: 99%
“…34 Similarly, another study found no difference in access to hospitalization or to CABG for racial and ethnic minorities under the Premier program. 35 Another ongoing P4P program is more precisely a penalty-for-performance program. The Hospital Readmissions Reduction Program, which launched in October 2012, penalizes hospitals with high readmission rates for AMI, HF, and pneumonia.…”
Section: Putting Dollars In Play: Pay For Performancementioning
confidence: 99%